THE ROLE OF THE NORTH SEA OIL RESOURCES IN NORWAY’S ECONOMY - D. A. Talagaeva; A. A. Trashchenko (Vestnik MGIMO-Universiteta, 2015)
Today Norway is a highly developed country with a predominantly service sector in the economic structure. However, oil continues to play a major role in the life of the state and society as one third of state revenues is based on oil resources, while export of raw materials totals more than a half of the country's overall export. However, it is not quite possible to cover the entire oil sector in Norway within the scope of one piece of work due to the differences in the characteristics of each of the three sources of the country's oil. In this context, the resources of the Norwegian and Barents Seas are associated with the problems of the Arctic and the Arctic law. At the same time, the North Sea is the most regulated area, besides it is the so called "homeland" of the oil production in Norway. Thus, this paper analyzes the role of the North Sea oil in the economy of Norway, which is the basis of its economic prosperity. Due to its oil revenues, Norway was once able to build a welfare state. Also the unique system of accumulation of oil revenues, which is reflected in the functioning of the Government Pension Fund of Norway, is a relevant issue as well. The article deals with the emergence of the oil industry in the country from a historical perspective, and analyzes its current state, including a detailed analysis of the existing fields and pipelines. Furthermore, the authors propose the estimation of state revenues from the oil production in the North Sea.